(untitled) (Journal of Academic Research, 2021)
Individuals show different levels of language proficiency that appears mostly in their lexical ability. A key factor of this variance is language exposure, however the quality and quantity are main determiners. For this purpose, this research examines the impact of diverse sources of the target language exposure on facilitating vocabulary acquisition in a non-native speaking community. The current study has been designed using the qualitative method approach to collect data from eight EFL learners enrolled in English department, Faculty of Art, Misrata University through semi-structured interviews. Further, the data have been analysed using thematic analysis. The research findings have revealed that communicative activities such as watching TV, listening to music, radio and podcast, reading, social media, video games, interaction with other speakers e.t. as informal sources of language exposure, can utterly improve vocabulary knowledge. Since, they provide a convenient environment and flexible amount of input. By contrast, classrooms instructive nature contradicts with the incidental mechanism of vocabulary acquisition and results in a good knowledge of grammatical structures in most cases. According to the participants, vocabulary development is tied to comprehensible input exposure beyond the formal setting. Based on the results, the incidental nature of vocabulary development requires informal exposure to the target language input. Recommendations of the study are: language teaching materials should be linked to informal language contact out of classroom, and further researches may include theories concerning vocabulary acquisition in relation to the practical side of the classroom.